2018
DOI: 10.1002/ece3.4608
|View full text |Cite
|
Sign up to set email alerts
|

Numerical response of mammalian carnivores to rodents affects bird reproduction in temperate forests: A case of apparent competition?

Abstract: Resource pulses such as mast seeding in temperate forests may affect interspecific interactions over multiple trophic levels and link different seed and nonseed consumers directly via predation or indirectly via shared predators. However, the nature and strength of interactions among species remain unknown for most resource pulse–driven ecosystems. We considered five hypotheses concerning the influence of resource pulses on the interactions between rodents, predators, and bird reproduction with data from north… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 58 publications
2
27
0
Order By: Relevance
“…Our study supports the low incidence of nest predation by small rodents found in nest camera studies elsewhere (Mallord et al 2012, Grendelmeier et al 2015, Bellamy et al 2018 , Grendelmeier et al 2018. If this hypothesis is correct, Wood Warblers could use rodent activity on the forest floor as an indicator of the predation risk from carnivores, which are particularly effective in predating the nests, to reduce the likelihood of nest failure by avoiding settling in areas of high rodent abundance , Grendelmeier et al 2018.…”
Section: Discussionsupporting
confidence: 81%
“…Our study supports the low incidence of nest predation by small rodents found in nest camera studies elsewhere (Mallord et al 2012, Grendelmeier et al 2015, Bellamy et al 2018 , Grendelmeier et al 2018. If this hypothesis is correct, Wood Warblers could use rodent activity on the forest floor as an indicator of the predation risk from carnivores, which are particularly effective in predating the nests, to reduce the likelihood of nest failure by avoiding settling in areas of high rodent abundance , Grendelmeier et al 2018.…”
Section: Discussionsupporting
confidence: 81%
“…It is well established that these Bresource pulses^ (Ostfeld et al 1996;Ostfeld and Keesing 2000) temporally release seed-eating rodents from food limitation and they become superabundant in the following spring (Pucek et al 1993;Ostfeld et al 1996;Ostfeld and Keesing 2000;Bogdziewicz et al 2016). Such rodent outbreaks extend over large spatial scales Knops 1998, 2000;Bogdziewicz et al 2017) and have negative consequences for ground-nesting songbirds Ostfeld 2003, 2008;, including wood warblers Grendelmeier et al 2018). Rodents per se are not a threat for wood warbler nests (cf Mallord et al 2012;Grendelmeier et al 2015); however, wood warblers and rodents are indirectly linked via shared enemies (apparent competition; Grendelmeier et al 2018).…”
Section: Communicated By P a Bednekoffmentioning
confidence: 99%
“…Such rodent outbreaks extend over large spatial scales Knops 1998, 2000;Bogdziewicz et al 2017) and have negative consequences for ground-nesting songbirds Ostfeld 2003, 2008;, including wood warblers Grendelmeier et al 2018). Rodents per se are not a threat for wood warbler nests (cf Mallord et al 2012;Grendelmeier et al 2015); however, wood warblers and rodents are indirectly linked via shared enemies (apparent competition; Grendelmeier et al 2018). It is welldocumented that generalist predators, e.g., martens and foxes, which are also important nest predators of wood warblers (Wesołowski 1985;Mallord et al 2012;Grendelmeier et al 2015), respond numerically and functionally to rodent outbreaks (Jędrzejewska and Jędrzejewski 1998;Ostfeld and Keesing 2000;Bogdziewicz et al 2016).…”
Section: Communicated By P a Bednekoffmentioning
confidence: 99%
See 1 more Smart Citation
“…Although negative correlations between rodents and wood warblers have been found at various spatial scales (Grendelmeier et al, 2019;Pasinelli et al, 2016;Szymkowiak & Kuczyñski, 2015;), there need not to be an underlying causality. It is well established that rodents respond positively to mast seeding (e.g., Pucek, Jedrzejewski, Jedrzejewska, & Pucek, 1993) and rodent hunters positively to increased rodent numbers (e.g., Grendelmeier et al, 2018;Schmidt & Ostfeld, 2003). Hence, wood warblers may use environmental cues related to mast seeding other than rodent or predator presence to decide where to settle.…”
Section: Discussionmentioning
confidence: 99%